2016
DOI: 10.1177/1362361315627134
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent boys with an autism spectrum disorder and their experience of sexuality: An interpretative phenomenological analysis

Abstract: Autism 0(0) 2 AbstractThis qualitative study explored how adolescent boys with autism spectrum disorder (ASD) experience their sexuality. Previous research has demonstrated that sexuality is a developmental task for boys with ASD, as it is for their peers. Case studies have suggested a relation between ASD and atypical sexual development; empirical studies on this subject, however, are scant and inconsistent. This study is based on interviews with eight boys, aged 16 to 20, with Asperger's disorder or autistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 35 publications
1
21
0
5
Order By: Relevance
“…Finally, we found no relation between sexuality and sexual development on the one hand, and ASD symptoms on the other. However, it should be noted that the literature on sexuality and ASDs in non-delinquent youth consists of both quantitative (e.g., Dewinter et al 2015 ) and qualitative studies (e.g., Dewinter et al 2016 ). To the best of our knowledge, however, sexuality and ASDs amongst JSOs have to date only been studied with a quantitative design, as we have done in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found no relation between sexuality and sexual development on the one hand, and ASD symptoms on the other. However, it should be noted that the literature on sexuality and ASDs in non-delinquent youth consists of both quantitative (e.g., Dewinter et al 2015 ) and qualitative studies (e.g., Dewinter et al 2016 ). To the best of our knowledge, however, sexuality and ASDs amongst JSOs have to date only been studied with a quantitative design, as we have done in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on how autistic traits affect autism and sexuality has primarily focused on the impacts of communication and social interaction differences. [13][14][15][16] For example, some autistic people report difficulty forming partnerships due to social communication challenges. 4,15 Autistic research participants also report anxiety related to social expectations of being in a relationship, and uncertainty about how to sexually satisfy their partner.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] For example, some autistic people report difficulty forming partnerships due to social communication challenges. 4,15 Autistic research participants also report anxiety related to social expectations of being in a relationship, and uncertainty about how to sexually satisfy their partner. 15 Some also report less com-mon sexual interests and sexual sensory fascinations that may impact sexual relationships.…”
Section: Introductionmentioning
confidence: 99%
“…There has been limited research into sexual education for autistic individuals relative to other intervention targets, such as social skills or communication (Holmes & Himle, 2014; Kellaher, 2015), in part because, historically, autistic individuals were mistakenly thought of as typically asexual or disinterested in relationships. However, recent literature including autistic youth without intellectual disability (ID) has contradicted this notion and found that sexuality and romantic relationships are important aspects of autistic life (Dewinter, Van Parys, Vermeiren, & van Nieuwenhuizen, 2017; Shattuck et al, 2012). Comparable numbers of autistic adults and adolescents have been found to have the same level of sexual interest and functioning as their TD peers (Byers, Nichols, & Voyer, 2013; Dewinter, Vermeiren, Vanwesenbeeck, Lobbestael, & Van Nieuwenhuizen, 2015; May, Pang, O’Connell, & Williams, 2017).…”
mentioning
confidence: 99%
“…However, parents of autistic youth struggle with how to teach these topics and often leave out discussions on relationships, sexual health and prevention, or general sexuality (Holmes & Himle, 2014). Many parents of autistic youth underestimate their child’s sexual experience and may be unaware of their child’s knowledge about sexuality, which may impact the type and amount of information they provide their child with about sexuality (Dewinter et al, 2017). Therefore, there is an explicit need for resources on sexuality for autistic youth and their families.…”
mentioning
confidence: 99%